Дослідження України в Антарктиці: поточна бібліографія. Публікації 2009–2010 рр. - Рибачук, В.П.; Віденіна, Н.Г. (Український антарктичний журнал, 2010)
Наведено бібліографічні описи наукових праць українських вчених з проблем дослідження Антарктики, опублікованих у вітчизняних і закордонних виданнях з січня 2009 по жовтень 2010 років. Представлений список поточної бібліографії доповнює і продовжує бібліографію вітчизняних публікацій за 2007–2009 рр., презентовану в попередньому випуску „Українського антарктичного журналу”. Приведены библиографические описания научных трудов украинских ученых по антарктической проблематике, опубликованных в отечественных и зарубежных изданиях с января 2009 по октябрь 2010 годов. Представленный список текущей библиографии дополняет и продолжает библиографию отечественных публикаций за 2007–2009 гг., опубликованную в предыдущем выпуске „Украинского антарктического журнала”. G.M. Dobrov Research Center for Scientific and Technical Potential and History of Science, National Academy of Sciences of Ukraine, 60 Taras Shevchenko Blvd., Kyiv 01032, Ukraine; Corresponding author: Victor P. Rybachuk, vnyugvpr@yandex.ru, rybachuk.v.p@nas.gov.ua. Abstract. The bibliographic descriptions of the Ukrainian scientific works on Antarctica that were published domestically and abroad in 2009 and 20010 as well as additional materials issued in 2008 are listed herein. This bibliographic data extends and complements the 2007–2009 current bibliography of national publications, presented in the "Ukrainian Antarctic Journal" in 2009 (issue 8). The abstracts were collected from Ukrainian scientific journals, collections, and conference proceedings as well as national (“Dzherelo”, “Litopys zhurnal'nykh statej”, etc.) and international (“Antarctic Bibliography”, Scopus, Google scholar, Scirus, e-Library) bibliographic databases. In total 148 publications were compiled on the topics of Antarctic research within the last two years. The references were arranged under the subject headings based on those used by the scientific issue "Ukrainian Antarctic Research" (V.P. Rybachuk, P.F. Gozhik, N.G. Videnina, and V.A. Litvinov, Ed. P.F. Gozhik, 2008, Kiev, Varta Publishers, 286 p., ISBN 978-966-02-4803-8).